The Therapeutic Range for Heparin Therapy: Relationship between Six Activated Partial Thromboplastin Time Reagents and Two Heparin Assays - Kitchen, S; Preston, F E (Thrombosis and Haemostasis, 1996)
The activated partial thromboplastin time (APTT) is the most commonly used test for laboratory monitoring of unfractionated heparin therapy. Since there are differences between APTT reagents in respect of responsiveness to heparin the widely used therapeutic range of 1.5-2.5 (APTT ratios) may not be appropriate for all reagents.The aim of this study was to assess the relationship between 6 different APTT reagents using a manual technique, 2 of these reagents used in combination with a coagulometer, a heparin assay by protamine titration and a chromogenic anti-Xa assay. Samples from 42 patients treated with unfractionated heparin for thromboembolic disease were studied, 12 of whom were receiving warfarin therapy with International Normalised Ratios (INR) of >1.3.For normal subjects, APTT results were highly dependent on the method used and statistically significant differences were noted. The ratio of patient to mean normal APTT was calculated for each APTT method. When 30 samples from heparinised patients (with INRs of <1.3) were analysed manually, the APTT ranges equivalent to 0.2-0.4 u/ml heparin by protamine titration (by regression analysis) were 1.6-1.9 for Boehringer reagent (the least responsive) up to 2.2-2.9 for Instrumentation Laboratory reagent (the most responsive). The concentration of heparin associated on average with APTT ratios of 1.5-2.5 varied approximately twofold to threefold between reagents.